Faktor-faktor yang mempengaruhi audit report lag - Christian Elrico Harison Lala; Lintje Kalangi; Anneke Wangkar (LPMP Imperium, 2022)
This research aims to determine whether company size, profitability, audit opinion, and auditor reputation significantly affect audit report lag. This research was conducted at property and real estate companies listed on the Indonesia Stock Exchange from 2018 to 2021. Return measures the natural logarithm of total assets, company size, and profitability on Assets (ROA). Audit opinion and auditor reputation are measured using the nominal scale with dummy variables. The type of this research is quantitative, with purposive sampling as the technique of selecting samples, and 26 companies were selected as samples. The data were analyzed using the multiple linear regression method. Based on the analysis results, it was proven that company size, profitability, and audit opinion had a significant effect on the audit report lag. Meanwhile, the reputation of a public accounting firm has no significant effect on audit report lag on property and real estate companies listed on the Indonesia Stock Exchange.